"It's in the Cards": The Contribution of Illustrated Metaphor Cards to Exploring Values Within Narratives. (January 2017) - Karnieli-Miller, Orit; Nissim, Geffen; Goldberg, Miriam
In this article, we present the use of illustrated metaphorical cards as a technique to enrich the qualitative narrative interview. We examine the advantages of incorporating a projective tool to assist in constructing and understanding personal narratives of people living with severe mental illness. We interviewed 25 participants—staff and members of a clubhouse in Israel (an international community model of rehabilitation in mental health)—and sought to understand their stories focused on personal and organizational values. The findings revealed that, in most cases, the cards contributed to data collection by enhancing the interviewees' ability for expression and by facilitating richer, more comprehensive stories and descriptions. This in turn enhanced the researcher's ability to understand the messages and stories presented. The research conclusions discuss the cards' potential contribution to improving data collection and analysis. The cards became an additional channel for expressing participants' experiences, emotions, and unique voice.